Komunikasi Dakwah Inovatif dan Perubahan Sosial: Studi Kasus pada Komunitas 'Ngaji Asyik Ahad Malam' di Street Cafe Surakarta - Hudah, Khoirul; Agus Suparno, Basuki (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
This research examines the religious communication strategy (da'wah) carried out by the 'Ngaji Asyik Ahad Malam' community at the Street Cafe Esemday, Mojosongo District, Surakarta City. Using qaualitative methods with an ethnographic approach, the results of this study show that millennials Muslims, those who join 'Ngaji Asyik Sunday Malam' tend to be less interested in the religious activities held in the formal and conventional manner, which require attending religious places such as mosques, mushalla, or Qur'an Learning Place (TPQ). However, millennials currently are more like religious activities that are elaborated in contemporary public spaces. In other words, they need the presence of innovative concepts for religious activities that are relevant and able to understand the millennial culture, and do not discredit them as well.